Psychology and Sufism Approaches to Narcissistic Personality Disorder (NPD): Toward an Integrative Model - Melisa Diah Maharani; Rida Luthfiana Wakhidah (UIN Sulthan Thaha Saifuddin Jambi, 2025)
Narcissistic Personality Disorder (NPD) has become an increasingly prevalent psychological issue in the digital era, often associated with maladaptive cognitions, fragile self-structures, and interpersonal dysfunction. While psychoanalytic and cognitive-behavioral approaches, including schema therapy, offer effective clinical interventions, they frequently face resistance and limitations in addressing the existential and moral dimensions of narcissism. In Islamic spirituality, narcissistic traits correspond to takabbur (arrogance), ujub (self-admiration), riya (ostentation), sum‘ah (seeking reputation), and hasad (envy), all of which are considered spiritual pathologies requiring tazkiyat al-nafs (purification of the soul). This study employs a conceptual and integrative literature review to synthesize psychological frameworks with Sufi teachings, proposing a three-level integrative model: (1) cognitive-behavioral restructuring, (2) emotional-spiritual regulation through practices such as muhāsabah and dhikr, and (3) existential reorientation grounded in zuhud. Findings suggest that integrating psychological therapies with Sufi practices enriches treatment by addressing not only symptoms but also the moral-spiritual roots of narcissism. The article concludes that this integrative framework offers both conceptual contributions to the literature on NPD and practical implications for culturally congruent counseling and psychotherapy in Muslim societies, while also providing a basis for future empirical validation.